If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-3)+4=5-(x+1)
We move all terms to the left:
2(x-3)+4-(5-(x+1))=0
We multiply parentheses
2x-(5-(x+1))-6+4=0
We calculate terms in parentheses: -(5-(x+1)), so:We add all the numbers together, and all the variables
5-(x+1)
determiningTheFunctionDomain -(x+1)+5
We get rid of parentheses
-x-1+5
We add all the numbers together, and all the variables
-1x+4
Back to the equation:
-(-1x+4)
2x-(-1x+4)-2=0
We get rid of parentheses
2x+1x-4-2=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2
| 59.95+7.33x=6.14 | | 4x-3x^2+8=0 | | 9x^2+6x=12 | | 8×b=27 | | 1/2r−3=3(4−2/3r) | | 3x+2+5x-4x=0 | | 7x+20=52-3x | | 12t^2-52t+40=0 | | |3-6x|=15 | | 25/3y+4/5=9/10 | | 1/3(9a+6)=-7 | | 3c+4=12+10. | | x+2=-2x+11 | | (3-x)/(1-2x)=5 | | 1/6(2x+2)=1/3 | | 6^m+3=36 | | 3^3r+1=81 | | (x-12)^2=27 | | 10^4=(x^2+1) | | 2^-x-2=2^6 | | X+(0.06xX)=5 | | 5^-2m=5^3m | | 3(v+7)÷-3=7(v-1)÷-9 | | x^2+13x-7=15 | | x/4=6/10 | | 6y=3×,y=1/2× | | 3^-3n=9 | | t^2-t-3/2=0 | | 6x-52=4x+46 | | 23+4m=÷2 | | 2.7(n+7.8)+6.5=9n-4 | | p2-33p+16=0 |